Influence of the emission site on the photoelectron circular dichroism in trifluoromethyloxirane. Issue 22 (27th May 2022) - Fehre, Kilian; Trinter, Florian; Novikovskiy, Nikolay M.; Grundmann, Sven; Tsitsonis, Dimitrios; Eckart, Sebastian; Bauer, Leonie; Hilzinger, Maria; Jahnke, Till; Dörner, Reinhard; Demekhin, Philipp V.; Schöffler, Markus S.
Abstract : The photoelectron circular dichroism is strongly influenced by the origin where the electron is set free. Abstract : We report a joint experimental and theoretical study of the differential photoelectron circular dichroism (PECD) in inner-shell photoionization of uniaxially oriented trifluoromethyloxirane. By adjusting the photon energy of the circularly polarized synchrotron radiation, we address 1s-photoionization of the oxygen, different carbon, and all fluorine atoms. The photon energies were chosen such that in all cases electrons with a similar kinetic energy of about 11 eV are emitted. Employing coincident detection of electrons and fragment ions, we concentrate on identical molecular fragmentation channels for all of the electron-emitter scenarios. Thereby, we systematically examine the influence of the emission site of the photoelectron wave on the differential PECD. We observe large differences in the PECD signals. The present experimental results are supported by corresponding relaxed-core Hartree–Fock calculations.